2005
DOI: 10.1002/jgm.819
|View full text |Cite
|
Sign up to set email alerts
|

Local stimulation of articular cartilage repair by transplantation of encapsulated chondrocytes overexpressing human fibroblast growth factor 2 (FGF-2)in vivo

Abstract: The data suggest that localized overexpression of FGF-2 enhances the repair of cartilage defects via stimulation of chondrogenesis, without adverse effects on the synovial membrane. These results may lead to the development of safe gene-based therapies for human articular cartilage defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 45 publications
5
109
0
4
Order By: Relevance
“…Many studies have implied a potent anabolic effect of bFGF on cartilage homeostasis and suggested its use for cartilage regeneration and repair (Cuevas et al, 1988;Cucchiarini et al, 2005;Hiraide et al, 2005;Inoue et al, 2006;Kaul et al, 2006;Deng et al, 2007;Schmal et al, 2007;Stewart et al, 2007). For example, Hiraide et al documented cartilage repair in an in vivo model of rabbit knee degeneration using an adeno-associated virus (AAV) to transport the bFGF gene into knee synovial tissue.…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have implied a potent anabolic effect of bFGF on cartilage homeostasis and suggested its use for cartilage regeneration and repair (Cuevas et al, 1988;Cucchiarini et al, 2005;Hiraide et al, 2005;Inoue et al, 2006;Kaul et al, 2006;Deng et al, 2007;Schmal et al, 2007;Stewart et al, 2007). For example, Hiraide et al documented cartilage repair in an in vivo model of rabbit knee degeneration using an adeno-associated virus (AAV) to transport the bFGF gene into knee synovial tissue.…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
“…In lapine articular cartilage, bFGF introduced via gene transfer was found to increase cell proliferation both in vitro and in vivo, suggesting its potential for repair and regeneration of cartilage defects (Kaul et al, 2006). Due to its proliferative capacity, several studies have identified bFGF as an anabolic factor in chondrogenesis and ECM homeostasis (Thompson et al, 1991;Kaul et al, 2006;Tsai et al, 2007).…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
“…Chemical methods, employed in preclinical studies, form complexes with DNA and various macromolecules, including liposomes, cationic polysaccharide and non-liposomal lipid-based transfection [14][15][16][17][18][19][20][21]. They can deliver large genes and are easy to produce on a large scale.…”
Section: Non-viral Vectormentioning
confidence: 99%
“…Such genes are insulin-like growth factor 1 (IGF-1) [15-18, 20, 23, 25], transforming growth factor β (TGF-β) [14,26,27], bone morphogenetic proteins (BMPs) [20,22] and fibroblast growth factor 2 (FGF-2) [16,18,21]. Other genes belong to the transcription factors family, SRY-related HMG box (SOX) [24], the anti-inflammatory cytokine Interleukin 10 (IL10) [12] and cartilage oligomeric matrix protein (COMP), a ECM component [19] (Table 1).…”
Section: Non-viral Vectormentioning
confidence: 99%
See 1 more Smart Citation